On the behavior of solutions of operator-differential equations at infinity - Butyrin, A.A. (Український математичний журнал, 1994)
The existence of limits at the infinity, generalized in the Abel sense, is established for bounded solutions of the operator-differential equation y′(t)=Ay(t) in a reflexive Banach space. У рефлексивному банаховому просторі встановлено існування узагальнених у розумінні Абеля границь на нескінченності для обмежених розв'язків операторно-диференціалного рівняння y′(t)=Ay(t).